Ratiometric Sensing of Hydrogen Peroxide Utilizing Conformational Change in Fluorescent Boronic Acid Polymers. (28th September 2017) - Takeshima, Kan; Mizuno, Kanako; Nakahashi, Hitoshi; Aoki, Hiroshi; Kanekiyo, Yasumasa
Abstract : We demonstrate that the copolymers containing boronic acid and pyrene units can be utilized for the fluorometric sensing of hydrogen peroxide (H2 O2 ) in aqueous solutions. The copolymer exists in a relatively extended conformation in the absence of H2 O2, whereas the polymer chain is contracted by the reaction of boronic acid moieties with H2 O2 to form phenol groups. This conformational change induces aggregation of the originally isolated pyrene groups. As a result, relative intensity of excimer emission with respect to monomer emission increases with H2 O2 concentration. Accordingly, the present methodology enables us to measure H2 O2 by means of ratiometric fluorescence change in the range of 0–30 μ M.